2022
DOI: 10.1021/jacs.1c11707
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Photocatalytic Water Splitting by Mimicking Photosystems I and II

Abstract: In nature, water is oxidized by plastoquinone to evolve O2 and form plastoquinol in Photosystem II (PSII), whereas NADP+ is reduced by plastoquinol to produce NADPH and regenerate plastoquinone in Photosystem I (PSI), using homogeneous molecular photocatalysts. However, water splitting to evolve H2 and O2 in a 2:1 stoichiometric ratio has yet to be achieved using homogeneous molecular photocatalysts, remaining as one of the biggest challenges in science. Herein, we demonstrate overall water splitting to evolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 49 publications
1
73
0
Order By: Relevance
“…340 As shown in Figure 57, the molecular models of PSI and PSII consist of two phases, a toluene and a water/trifluoroethanol mixture (H 2 O/TFE, 3:1 v/v) phase, respectively, and the two phases are separated by a liquid membrane. 340 Then the toluene phase of the PSII model was connected to the same phase of the PSI model, and the water/trifluoroethanol phase of the PSII model was also connected to the same phase of the PSI model by two glass membranes, respectively. 340 The PSII model contains plastoquinone analogues [p-benzoquinone derivatives (X-Q)] in toluene and an iron(II) complex ([(N4Py)Fe II ] 2+ ) as a molecular water oxidation catalyst in H 2 O/TFE (3:1 v/v), which resulted in evolution of the stoichiometric amount of O 2 and generation of hydroquinone derivatives (X-QH 2 ).…”
Section: Combination Of Molecular Models Of Psi and Psiimentioning
confidence: 99%
“…340 As shown in Figure 57, the molecular models of PSI and PSII consist of two phases, a toluene and a water/trifluoroethanol mixture (H 2 O/TFE, 3:1 v/v) phase, respectively, and the two phases are separated by a liquid membrane. 340 Then the toluene phase of the PSII model was connected to the same phase of the PSI model, and the water/trifluoroethanol phase of the PSII model was also connected to the same phase of the PSI model by two glass membranes, respectively. 340 The PSII model contains plastoquinone analogues [p-benzoquinone derivatives (X-Q)] in toluene and an iron(II) complex ([(N4Py)Fe II ] 2+ ) as a molecular water oxidation catalyst in H 2 O/TFE (3:1 v/v), which resulted in evolution of the stoichiometric amount of O 2 and generation of hydroquinone derivatives (X-QH 2 ).…”
Section: Combination Of Molecular Models Of Psi and Psiimentioning
confidence: 99%
“…These characteristics point to the potential of homogenous photocatalysts, which can be used at low concentrations due to high molar absorptivity. [ 27 ] Furthermore, it was recently shown that it is theoretically possible for homogeneous photocatalysts to achieve dual absorber STH efficiencies (>20%) with a single catalyst. [ 28 ] With progress on catalyst concentration and STH efficiency, there is a pathway for PC to cost‐competitive hydrogen production.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, simultaneous multi-electron reduction and oxidation reactions, e.g., overall water splitting [19][20][21][22] and CO 2 reduction using water as the electron source, 16 have been accomplished using a number of semiconductor photocatalysts, while such reactions have hardly been reported using a molecular photocatalyst system. 23 In terms of CO 2 reduction, however, semiconductor photocatalysts frequently suffer from the low selectivity of CO 2 reduction by competing with efficient proton reduction. 16 Recently, molecular-semiconductor hybrid photocatalysts have been developed to maximize their advantages, although it still remains a challenge for efficient photocatalytic CO 2 reduction.…”
Section: Introductionmentioning
confidence: 99%